Efektivitas Air Rebusan Daun Sirih Merah terhadap Penurunan Kadar Gula Darah pada Pasien Diabetes Melitus di Wilayah Kerja Puskesmas Saling 2018 - Listiana, Devi; Effendi, Effendi; Indriati, Bela (JURNAL KEPERAWATAN MUHAMMADIYAH BENGKULU, 2019)
Diabetes mellitus is a chronic disease that occurs due to the pancreas not being able to produce enough insulin or when the body cannot effectively use the insulin. The purpose of this study was to study the effectiveness of the provision of red betel leaf boiled water on reducing blood sugar levels of Diabetes Mellitus patients in the Saling Puskesmas District of Four Lawang in 2018. The design of this study was an experimental Quasy using The One Group Pretest - Postest Design, technique data collection using primary and secondary data. The population of this study were all Diabetes Mellitus patients in the Saling Community Health Center in July-August 2018, amounting to 16 people, sampling was done by accidental sampling. The results of the study, from 16 patients with diabetes mellitus there are 9 people (56.2%) with blood sugar levels less than 200 mg / dl. Wilcoxon Sign Rank test results obtained value Z = -3.517 with p = 0.000 0.05 means significant. So the two variables have different medians, there are differences in the GDS levels of Diabetes Mellitus patients before and after administration of red betel leaf decoction water. Conclusion, Red betel leaf decoction water is significantly effective in reducing blood sugar levels in patients with diabetes mellitus. It is expected that Puskesmas staff can increase public knowledge by counseling about red betel leaves as a Non-Pharmacological drug for patients with Diabetes Mellitus who do not experience complications.Â Keywords: Red Betel Leaf Decoction Water, Diabetes Mellitus, Blood Sugar Levels